2011
DOI: 10.3390/md9081368
|View full text |Cite
|
Sign up to set email alerts
|

Three New Compounds from Aspergillus terreus PT06-2 Grown in a High Salt Medium

Abstract: To investigate the structurally novel and bioactive natural compounds from marine-derived microorganisms under high salinity, the fungus Aspergillus terreus PT06-2 was isolated from the sediment of the Putian Sea Saltern, Fujian, China. Three new compounds, terremides A (1) and B (2) and terrelactone A (3), along with twelve known compounds (4–15) were isolated and identified from the fermentation broth of A. terreus PT06-2 at 10% salinity. Among these metabolites, compounds 4 and 15 only produced in the 10% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 32 publications
1
59
0
1
Order By: Relevance
“…A study carried out by Kumar et al (2000) showed the production of an inhibition zone by A. terreus against Neurospora crassa . Moreover, a study by Wang et al (2011) revealed that new compounds from A. terreus could produce inhibition zone against Pseudomonas aeruginosa and Enterobacter aerogenes growth. It is likely that an inhibition zone was produced because A. terreus secrets metabolites that interfere with the growth of P. aphanidermatum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out by Kumar et al (2000) showed the production of an inhibition zone by A. terreus against Neurospora crassa . Moreover, a study by Wang et al (2011) revealed that new compounds from A. terreus could produce inhibition zone against Pseudomonas aeruginosa and Enterobacter aerogenes growth. It is likely that an inhibition zone was produced because A. terreus secrets metabolites that interfere with the growth of P. aphanidermatum .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that an inhibition zone was produced because A. terreus secrets metabolites that interfere with the growth of P. aphanidermatum . Ferrón et al (2005) and Wang et al (2011) reported the production of terremides A and B and lovastatin by A. terreus that were found responsible for the production of inhibition zones. In our study, the use of CF from A. terreus isolates resulted in electrolyte leakage in P. aphanidermatum mycelium and also interfered with oospore production in P. aphanidermatum .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Butyrolactones were mainly found as metabolites from fungi and high plants in nature. 4 They appeal to medicinal chemists because of their pronounced pharmacological effects including antibacterial, 5,6 anti-tumor, 7,8 anti-inflammatory, 9,10 anti-virus, 11,12 and the like.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is produced by the strain Aspergillus terreus [9] and is reported to have antimicrobial, cytotoxic, nematicidal, and phytotoxic activities [10].…”
Section: R(-)-6-hydroxymellein (3) Colorless Solid Crystal (Etoac Mmentioning
confidence: 99%